1990
DOI: 10.1111/j.2042-7158.1990.tb07033.x
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Uptake by the Rat Gastrointestinal Mucosa: Quantitation and Particle Size Dependency

Abstract: Polystyrene microspheres in the size range 50 nm to 3 microns were fed by gavage to female Sprague Dawley rats daily for 10 days at a dose of 1.25 mg/kg-1. Previous histological evidence of the uptake of these particles and their absorption across the gastrointestinal tract and passage via the mesentery lymph supply and lymph nodes to the liver and spleen was confirmed by analysis of tissues for the presence of polystyrene by gel permeation chromatography. Measurement of radioactivity of tissues following admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
414
2
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 828 publications
(440 citation statements)
references
References 18 publications
17
414
2
7
Order By: Relevance
“…It can be assumed that the lowest amount of GN size 50 nm in the lymph nodes was caused by their large size, hindering absorption in the gastrointestinal tract. This thesis is confirmed by studies of P. Jani et al [9], in which the size-dependent effect of suction polystyrene particles (from 50 nm to 3000 nm) was detected. It is interesting to note the fact that at the sizes of 15 nm GN the number of aurosomes in all zones of the lymph nodes increases almost proportionally to the Table 1.…”
Section: Resultssupporting
confidence: 74%
“…It can be assumed that the lowest amount of GN size 50 nm in the lymph nodes was caused by their large size, hindering absorption in the gastrointestinal tract. This thesis is confirmed by studies of P. Jani et al [9], in which the size-dependent effect of suction polystyrene particles (from 50 nm to 3000 nm) was detected. It is interesting to note the fact that at the sizes of 15 nm GN the number of aurosomes in all zones of the lymph nodes increases almost proportionally to the Table 1.…”
Section: Resultssupporting
confidence: 74%
“…Of the various innate immune cells, lipid nanoparticles accumulated with higher efficiency in monocytes 164 and macrophages 165 than in lymphocytes, neutrophils, and dendritic cells. After oral administration or intravenous injection into mice, polystyrene nanoparticles 24 and iron oxide nanoparticles 166 were both detected in bone marrow.…”
Section: Hematopoietic Toxicitymentioning
confidence: 99%
“…Morevover, the high surface-to-volume ratio displayed by nanoparticles increases drug loading capacity (de la Fuente et al, 2008a). Previous studies have demonstrated that nanoparticle contact with epithelial surfaces is maximised when they display a size within 50 and 500 nm (Desai et al, 1996;Jani et al, 1990) and a strongly positive zeta potential (Bogataj et al, 2003;Carvalho et al, 2010).…”
Section: Introductionmentioning
confidence: 99%